Correlation Between Work Motivation Towards Caring Behaviour of Nurse at the Inpatient Ward of Class III - Ery Purwanti; Suci Lestari; Eka Novyriana (Global Health Science Group, 2020)
Caring is an important basic that can make it as a core of whole nursery practice by increasing caring and dynamic approacing to help patient healing process that one of them is influenced by work motivation. Work motivation become an important factor for nurse in running their role as a nursing care person. The aim of this research is to find out the correlation between work motivation toward nurse caring behaviour, using quantitatif method with correlation design that draw a phenomenon that happened by combining two variables with Kendall Taus’ test using cross sectional approach. Research sample is 28 nurses with total sampling model. Technique of collecting the data is using questionnaire that already tested the validity with the result of alpha cronbach is >0.7 which is 0.936 for work motivation and alpha cornbach >0.7 which is 0.973 for caring behaviour. From the research result can be found out that the result of work motivation is mostly high (60.7%) and so for nurse caring behaviour (71.4%). From Kendall Tau correlation test gained result r value is 0.462 with significance value is 0.016. So it can be summarized that there is correlation between work motivation toward nurse caring behaviour at the inpatient ward of class III.